The Y chromosome of autochthonous Basque populations and the Bronze Age replacement - Javier Rodriguez Luis (Nature Portfolio, 2021)
Abstract Here we report on the Y haplogroup and Y-STR diversity of the three autochthonous Basque populations of Alava (n = 54), Guipuzcoa (n = 30) and Vizcaya (n = 61). The same samples genotyped for Y-chromosome SNPs were typed for 17 Y-STR loci (DYS19, DYS385a/b, DYS398I/II, DYS390, DYS391, DYS392, DYS393, DYS437, DYS438, DYS439, DYS448, DYS456, DYS458, DYS635, Y-GATA H4) using the AmpFlSTR Yfiler system. Six major haplogroups (R, I, E, J, G, and DE) were detected, being R-S116 (P312) haplogroup the most abundant at 75.0% in Alava, 86.7% in Guipuzcoa and 87.3% in Vizcaya. Age estimates for the R-S116 mutation in the Basque Country are 3975 ± 303, 3680 ± 345 and 4553 ± 285 years for Alava, Guipuzcoa and Vizcaya, respectively. Pairwise Rst genetic distances demonstrated close Y-chromosome affinities among the three autochthonous Basque populations and between them and the male population of Ireland and Gascony. In a MDS plot, the population of Ireland segregates within the Basque cluster and closest to the population of Guipuzcoa, which plots closer to Ireland than to any of the other Basque populations. Overall, the results support the notion that during the Bronze Age a dispersal of individuals carrying the R-S116 mutation reached the Basque Country replacing the Paleolithic/Neolithic Y chromosome of the region.